The Effectiveness of Picture: An Empirical Evidence in Vocabulary Mastery - Dakhi, Saniago; Maritha, Ema (JET (Journal of English Teaching), 2017)
This action research was conducted to improve the students’ English vocabulary mastery by using picture. To achieve the objective, data were collected through the test, questionnaire and observation from 21 students in third graders of SDN Karawang Kulon II. The outcomes of the research showed that students’ vocabulary mastery got improved. This improvement is seen from the mean score of the test, i.e. 56.19 (Pre-test I), 81.90 (Post-test II), and 94.29 (Post-test II). Additionally, the result of questionnaire on the vocabulary teaching applying picture also shows the positive changes. The above data indicates that vocabulary picture can be effective media for vocabulary learning English. However, it is expected that other researchers could conduct similar researches on the related issues to develop it.